Comment on "On the tensile strength distribution of multiwalled carbon nanotubes" [Appl. Phys. Lett. 87, 203106 (2005)] - Lu, Chunsheng (American Institute of Physics, 2008)
In a recent letter, Barber, Andrews, Schadler, and Wagner, Appl. Phys. Lett. 87, 203106 (2005). indicated that Weibull-Poisson statistics could accurately model the nanotube tensile strength data, and then concluded that the apparent strengthening mechanism in a multiwalled carbon nanotube (MWCNT) grown by chemical vapor deposition (CVD) is most likely caused by an enhanced interaction between the walls of the nanotube. In this comment, we show that their conclusion seems to be inconsistent with the assumption introduced in the data analysis by using a two-parameter Weibull distribution. Further statistical analysis provides a new explanation on the scattered strengths of MWCNTs. The effectiveness of Weibull-Poisson statistics at nanoscales is also discussed. ©2008 American Institute of Physics